Educational Dissemination for the Implementation of the Covid-19 Health Protocol at Mawar Paud Posts - Sitti Anggraini; Agnes Dona Tekla (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
In this time of the COVID-19 pandemic, it is important to educate children about health protocols. Education on the application of this health protocol is intended so that children at the Mawar Paud Post can understand and know the health protocols that must be applied, namely the 5 M, namely washing hands, maintaining distance, wearing masks, limiting interactions, and staying away from crowds. Based on observations and interviews conducted with early childhood children at the Mawar Paud Post, it was found that there were still many children who did not apply the health protocol (5 M), namely 1) There were still many children who did not wash their hands when entering the classroom, in the event that water and soap have been prepared to wash their hands in front of the class, 2) They don't keep their distance in class, they tend to still like to gather closely with their friends, 3) There are still many preschool children who don't wear masks in the classroom. in the classroom and in the school environment, 4). Do not limit the interaction of fellow friends at school, 5). Do not stay away from the crowd when in the school environment or in the classroom. Early childhood is an important asset for the future of a nation, therefore an effort is needed to introduce them to be able to understand and implement the Covid-19 health protocol effectively. The method used is the experimental design method. To see the results of education based on a questionnaire obtained from pre-test-post-test data. The results showed that there was an increase in knowledge between before being given education on COVID-19 health protocols and after being given education on Covid-19 health protocols.